A study on non-malignant lesion of larynx - Mathan M., Bharathi Mohan; D. K., Selvam; V. J., Vikram (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2018)
Background: Benign laryngeal lesions are a spectrum of laryngeal diseases where symptoms vary from discomfort in throat, pain in throat, change of voice to stridor. Prompt diagnosis and intervention will reverse the conditions in certain laryngeal lesions. Methods: A prospective study was carried out in department of ENT, Madras Medical College/Institute of Child Health, Chennai between August 2013-November 2015 of non-malignant lesions of larynx. All these cases underwent a thorough ENT examination, examined under direct laryngoscope or micro laryngeal examination as the situation warrants. Benign non –neoplastic lesions are usually treated by excision biopsy and the biopsy results were confirmed. Results: This study included 50 cases of non-malignant lesions of larynx. In our study 34% of the cases fall in the age group of 20-30 years, followed by 22% in age group of 0-10 years. The mean age group was 26 years. Males were 72% and female constituted 28%. The hoarseness is the common symptom in 36 patients, while stridor was the predominant symptom in 14 patients. The treatment modality followed were micro laryngeal excision in 40 cases, tracheostomy in 6 cases. Conclusions: Management of the non-malignant lesions of larynx, by early diagnosis with effective conservative management in the initial stages, will reduce the necessity of the surgery. Counselling, voice rehabilitation, micro laryngeal surgery is the best modality.